The effect of skilled emigration on real exchange rates through the wage channel - Alice Y. Ouyang; Saumik Paul (Asian Development Bank Institute (ADBI), 2018)
Building on an analytical model, we provide cross-country empirical evidence that net skilled emigration appreciates bilateral real exchange rates through the wage channel in source countries. Chains of causality in the presence of the Law of One Price run through the "spending effect" and the "resource allocation effect," analogous to the remittance-based Dutch disease effect. A pricing-to-market model allows pass-through for both traded and nontraded prices when the Law of One Price is violated. The skilled emigration elasticity of real exchange rate is estimated to be in the range of between .6 and .8, with internal prices playing a dominant role. Alternative model specifications show robust outcomes.
Keywords: F22; F31; 330; emigration; exchange rate; the Dutch disease